Application of amphiphilic fluorophore-derived nanoparticles to provide contrast to human embryonic stem cells without affecting their pluripotency and to monitor their differentiation into neuron-like cells. (15th September 2018) - Zhou, Shixin; Zhao, Hongxi; Feng, Ruopeng; Ding, Lan; Li, Zhiqiang; Deng, Changwen; He, Qihua; Liu, Yinan; Song, Bo; Li, Yang
Graphical abstract: Abstract: Fluorogenic labeling is a potential technique in biology that allows for direct detection and tracking of cells undergoing various biological processes. Compared to traditional genetic modification approaches, labeling cells with nanoparticles has advantages, especially for the additional safety they provide by avoiding genomic integration. However, it remains a challenge to determine whether nanoparticles interfere with cell traits and provide long-lasting signals in living cells. We employed an amphiphilic fluorophore-derived nanoparticle (denoted by TPE-11) bearing a tetraphenylethene (TPE) moiety and two ionic heads; this nanoparticle has an aggregation-induced emission (AIE) effect and the ability to self-assemble. TPE-11 exhibited the property of higher or longer fluorescence intensities in cell imaging than the other two nanomaterials under the same conditions. We used this nanomaterial to label human embryonic stem (hES) cells and monitor their differentiation. Treatment with low concentrations of TPE-11 (8.0 μg/mL) resulted in high-intensity labeling of hES cells, and immunostaining analysis and teratoma formation assays showed that at this concentration, their pluripotency remained unaltered. TPE-11 nanoparticles allowed for long-term monitoring of hES cell differentiation into neuron-like cells; remarkably, strong nanoparticle signals were detected throughout the nearly 40-day differentiation process. Thus, these results demonstrate that the TPE-11 nanoparticle has excellent biocompatibility for hES cells and is a potential fluorogen for labeling and tracking the differentiation of human pluripotent stem cells. Statement of Significance: This study uses a nanoparticle-based approach to label human embryonic stem (hES) cells and monitor their differentiation. hES cells are distinguished by two distinctive properties: the state of their pluripotency and the potential to differentiate into various cell types. Thus, these cells will be useful as a source of cells for transplantation or tissue engineering applications. We noticed the effect of aggregation-induced emission, and the ability to self-assemble could enhance the persistence of signals. Treatment with low concentrations of TPE-11 nanoparticles showed high-intensity labeling of hES cells, and immunostaining analysis and teratoma formation assays showed that at this concentration, their pluripotency remained unaltered. Additionally, these nanoparticles allowed for long-term monitoring of hES cell differentiation into neuron-like cells lasting for 40 days.